Kreuth III: European consensus proposals for treatment of haemophilia with coagulation factor concentrates. (May 2014) - Giangrande, P.; Seitz, R.; Behr‐Gross, M. E.; Berger, K.; Hilger, A.; Klein, H.; Schramm, W.; Mannucci, P. M.
Summary This report summarizes recommendations relating to haemophilia therapy arising from discussions among experts from 36 European countries during the Kreuth III meeting in April 2013. To optimize the organization of haemophilia care nationally, it is recommended that a formal body be established in each country to include the relevant clinicians, national haemophilia patient organization, health ministry, paying authority and (if appropriate) regulatory authorities. The minimum factor VIII consumption level in a country should be 3 I.U. per capita. Decisions on whether to adopt a new product should not be based solely on cost. Prophylaxis for children with severe haemophilia is already recognized as the optimum therapy. Ongoing prophylaxis for individual adults should also be provided when required based on clinical decision making by the clinician in consultation with the patient. Children with inhibitors who have failed, or who are not suitable for, immune tolerance therapy should be offered prophylaxis with bypassing agents. Single factor concentrates should be used as therapy wherever possible in patients with rare bleeding disorders. Orphan drug designation for a factor concentrate should not be used to hinder the development, licencing and marketing of other products for the same condition which have demonstrably different protein modification or enhancement.